APLIKASI MESIN BOR DI INDUSTRI PANDE BESI - Seno Darmanto; Didik Purwadi; Hartono Hartono; Mohd. Ridwan; Didik Ariwibowo; Yusuf Umardani; Yuniarto Yuniarto (Jurnal Pengabdian Vokasi, 2021)
The PKUM scheme service activities for the Iron Pande Industry Group are carried out to improve the quality of production and export-based management. There are dozens of large, medium and small scale iron pande industries in Rejosari Pakis Magelang in Central Java and one of them is a member of the Mijil Karya group. The development of facilities for members of the iron pane industry is aimed at increasing the capacity / productivity and quality of iron pane products and carved bamboo furniture. And to achieve the capacity and quality of local content-based iron products and with local and national market share (exports), the service team prepares work steps or service activities including deepening company management management, especially in the flow of materials or goods and finance, deepening of improvements and improvements production units, deepening the improvement and refinement of local and national scale marketing (exports), completing showrooms to support marketing, implementation in partner industries and formulating indicators of success. In principle, a seated drilling machine consists of a leg or a base, an electric motor, a table, a power transmission, a hand-feed lever, a vise, a clamp set, an anvil (parallel block), a chuck, a reduction case, an opening peg, a boring head and a eye drill. Testing of drill tools with brass material showed an increase in drill feeding speed and effective drilling time at 1400 rpm. Meanwhile, testing of drilling tools using Cast Iron ST 20 also shows that it is effective at 960 rpm